2023
DOI: 10.3390/ijms24129928
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of β-Glucosidase Production in a Crude Aspergillus japonicus VIT-SB1 Cellulase Cocktail Using One Variable at a Time and Statistical Methods and its Application in Cellulose Hydrolysis

Abstract: Pulp and paper mill sludge (PPMS) is currently disposed of into landfills which are reaching their maximum capacity. Valorisation of PPMS by enzymatic hydrolysis using cellulases is an alternative strategy. Existing commercial cellulases are expensive and contain low titres of β-glucosidases. In this study, β-glucosidase production was optimised by Aspergillus japonicus VIT-SB1 to obtain higher β-glucosidase titres using the One Variable at a Time (OVAT), Plackett Burman (PBD), and Box Behnken design (BBD)of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
2
0
0
Order By: Relevance
“…The p value < 0.05 indicates the significance of the corresponding factors, with the incubation time, KCl, NaCl, Bambara concentration, and agitation speed with p values ranging from <0.0001 to 0.0062 were established as the most significant factors (Table 4). These results are in agreement with the previous studies that identified incubation time [19,41] and agitation speed [38,41] as significant factors in Bgl production by different microorganisms. However, a negative correlation between KCl concentration and enzyme production was observed in this study; this is in contrast to a study on Aspergillus versicolor, where the same salt displayed a positive relationship with Bgl production [38].…”
Section: Screening Of Significant Variables By Plackett-burman Designsupporting
confidence: 93%
See 1 more Smart Citation
“…The p value < 0.05 indicates the significance of the corresponding factors, with the incubation time, KCl, NaCl, Bambara concentration, and agitation speed with p values ranging from <0.0001 to 0.0062 were established as the most significant factors (Table 4). These results are in agreement with the previous studies that identified incubation time [19,41] and agitation speed [38,41] as significant factors in Bgl production by different microorganisms. However, a negative correlation between KCl concentration and enzyme production was observed in this study; this is in contrast to a study on Aspergillus versicolor, where the same salt displayed a positive relationship with Bgl production [38].…”
Section: Screening Of Significant Variables By Plackett-burman Designsupporting
confidence: 93%
“…4d). According to literature and the results obtained in this study, it can be inferred that further increase in Bgl production in different microorganisms is possible by optimization of medium components and physical components via statistical methods [38,41].…”
Section: Optimization By Central Composite Design and Model Validationsupporting
confidence: 53%